SHAVASANA: HARMONI DAN PENYEMBUHAN PENYAKIT TUBUH DAN PIKIRAN - Pradnya, I Made Adi Surya (JURNAL YOGA DAN KESEHATAN, 2018)
Present era, people are faced with competition of various aspects, resulting in a culture of high tension. The tension that occurs causes the anatomy of the body is disturbed, even the damage that causes the balance of the body and mind problems. This disharmony becomes a common illness, stress, a psychosomatic disorder that can only be healed through inward healing or relaxation. Yoga is one method to overcome the problem and restore harmony between body and mind, so it can be felt directly on health. Asana is part of yoga. Asana has many postures. For deep relaxation can be done with shavasana. Through the shavasana the body and mind enter into relaxation and release the tension from the whole anatomy of the body. Similarly, shavasana can cure stress because replacing the negative emotional sediment in the self into a positive emotion. Stress occurs when a person can not solve the problem that comes due to the difference between the desire with reality. Therefore, shavasana through proper relaxation and breathing and done at the right time, psychosomatic illness can be cured.